A Queer Protocol of Homage: Chambres de Ténèbres/Tombeau de Claude Vivier By Marko Nikodijević - Novak, Jelena (International Journal of Music New Sound, 2007)
The music of Canadian composer Claude Vivier (1948-1983) was used as a fractalized material for the creation of the composition Chambres de ténèbres/tombeau de Claude Vivier (2005) by Marko Nikodijević. Vivier’s opus and his marginal queer acting were the pillars of Nikodijević’s meticulous reading/deconstructing of Vivier’s world through his own artistic dilemmas.